Computational analysis of a flapping uvula on aerodynamics and pharyngeal wall collapsibility in sleep apnea. (20th September 2019) - Wang, Junshi; Xi, Jinxiang; Han, Pan; Wongwiset, Niphattha; Pontius, John; Dong, Haibo
Abstract: Studying the airflows and the resultant aerodynamic pressure/force in the pharyngeal airway is critical for understanding the pathophysiology of snoring and sleep apnea. In this work, an experiment-driven computational study was conducted to examine the aerodynamics in human pharyngeal airway. An anatomically accurate pharynx model associated with different uvula kinematics was reconstructed from human magnetic resonance image (MRI) and high-speed photography. An immersed-boundary-method (IBM)-based direct numerical simulation (DNS) flow solver was adopted to simulate the corresponding unsteady flows in all their complexity. Analyses were performed on vortex dynamics and pressure fluctuations in the pharyngeal airway and force oscillations on the pharyngeal wall under the influence of varying airway obstructions, uvula flapping mode, and uvula flapping frequencies. It was found the vortex formation, aerodynamic pressure, and pharyngeal wall force were significantly affected by the width of the pharyngeal airway. By contrast, the influences from the uvula flapping mode were insignificant when other parameters were similar. Fast Fourier transformation (FFT) and continuous wavelet transform (CWT) analysis of the pressure time history revealed the existence of higher order harmonics of base frequency with significant pressure amplitudes and energy intensities. It was also found the airway pressure and pharyngeal wall force oscillate more dramatically at higher uvula flapping frequencies, which tends to promote the collapse of pharyngeal wall and initiates sleep apnea.